Le Saladin de Farah Antūn du mythe littéraire arabe au mythe politique - Luc-Willy Deheuvels (Université de Provence, 2000)
A major change has taken place in the Arab world as regards the two « Saladins » : on one hand the ideal prince establishing a unified power, the champion of a just jihäd whose image was forged in the 7th/13th century, and the other the hero of great contemporary Arab causes. This evolution goes back to the last years of the previous century and he first decades of the 20th century, a period which coincides with the appearance of Saladin in modern Arabic literature by way of the new genres (theatre and romantic fiction). This particular phase of the history of the Saladin myth is explained in the article, focusing on a work which has played an important role in this mutation : the play writen in 1914 by par Farah Antūn, al-Sultän Saläh al-din wa-mamlakat Urûshalïm [Sultan Saladin and the kingdom of Jerusalem]. The text, the production and the reception of the play are analyzed to show how the mythical figure is born within a founding narrative, and how the image of the virtuous, liberating and unifying chief is constructed of the Muslim prince idealized by the ancient sources. Farah Antūn has created a mythical figure of a politico-heroic type responding to the expectations of the Arab world's collective psyche.